The importance of storytelling in nursing education (Research, Society and Development, 2021)
This study aims to identify the evidence available in the literature on the use of storytelling as a learning strategy in nursing education. This is a scope review using the Joanna Briggs Institute methodology, carried out in the PubMed, Scielo, ERIC, Science Direct and Lilacs databases, using the Boolean operators “AND” and “OR”. Original studies published until August 2021 were reviewed. Of the 42 productions analyzed in full, 21 comprised the sample, and were published between 1998 and 2020 in six countries, including the United Kingdom, United States of America, Australia, Canada, Norway and Sweden. Among the types of research included, qualitative (14.3%) and descriptive (14.3%) studies stood out. As for the theme of the narratives, clinical experiences (42.9%) and patients' stories (19%) were identified as the most discussed, and the most used resource was digital media (53.6%). Benefits of the use of storytelling in nursing education were evidenced, including: developing and/or increasing empathy, attracting attention, forming the theory-practice link, improving understanding and training. These contributions enable a differential training of the professional, providing a comprehensive, differentiated and humanized view of the patient. However, some disadvantages are associated with its use, such as the storyteller's vulnerability and discomfort due to the emotional impact. The evidence demonstrates the applicability of the methodology, with the narrative content and the resources used being important attributes for its effectiveness. It is suggested that future researches expand their studied samples in order to compose a solid base that promotes the validation of this tool.